Chloroplast development activates the expression of ascorbate biosynthesis-associated genes in Arabidopsis roots. (July 2019) - Shiroma, Saki; Tanaka, Mio; Sasaki, Tomohiro; Ogawa, Takahisa; Yoshimura, Kazuya; Sawa, Yoshihiro; Maruta, Takanori; Ishikawa, Takahiro
Highlights: Chloroplast development activates the expression of ascorbate biosynthesis-associated genes in roots exposed to light. The chloroplast-dependent activation is suppressed by a photosynthetic inhibitor. A null mutation in the LONG HYPOCOTYL 5 ( HY5 ) gene almost completely inhibited root greening as well as the VTC2 expression. Abstract: Transcriptional activation of ascorbate biosynthesis-associated genes under illumination is one of the important steps in ascorbate pool size regulation in photosynthetic tissues. Several biological processes within chloroplasts such as photosynthesis are required for this activation, suggesting functional chloroplasts to play a key role. We herein found that when grown on agar plate, ascorbate content in Arabidopsis non-photosynthetic tissues, roots, are unexpectedly almost comparable to that in shoots. The high accumulation of ascorbate was particularly observed in root regions closer to the root-hypocotyl junction, in which chloroplast development occurred because of a direct exposure to light. When chloroplast development in roots were further stimulated by shoot removal, the expression of biosynthetic genes, especially VTC2 gene that encodes GDP-l -galactose phosphorylase, was activated, resulting in an increase in ascorbate pool size. These positive effects were canceled when the roots were treated with a photosynthetic inhibitor. A null mutation in the LONG HYPOCOTYL 5 ( HY5 ) gene almost completely inhibited root greening as well as the VTC2 expression. Overall, these findings show that chloroplast development can trigger the expression of ascorbate biosynthesis-associated genes not only in leaves but also in roots.